Anemia in Mexican women: a public health problem Anemia en mujeres mexicanas: un problema de salud pública - Teresa Shamah-Levy; Salvador Villalpando; Juan A. Rivera; Fabiola Mejía-Rodríguez; Martha Camacho-Cisneros; Eric A Monterrubio (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: The purpose of this study is to quantify the prevalence and distribution of anemia among women of childbearing age (12 to 49 years) participating in the 1999 National Nutrition Survey (NNS-1999). MATERIAL AND METHODS: The survey had a probabilistic design and was representative at the national level, of urban and rural areas and four regions: North, South, Center, and Mexico City. Hemoglobin concentration was determined in capillary blood samples using a portable photometer (HemoCue), in 17 194 women, 697 of whom were pregnant. RESULTS: The overall prevalence of anemia was 27.8% in pregnant women and 20.8% in non-pregnant women. Higher prevalences were observed in rural as compared to urban areas, both in pregnant (28.0% vs 27.7%) and non-pregnant (22.6% vs 20.0%) women, but the differences were not statistically significant (p >0.05). Women in the South had the greatest prevalence (23.2%), followed by those in the North (20.9%), Center (20.6%), and Mexico City (16.4%). Non-pregnant indigenous women had a prevalence of 24.8%, while in non-indigenous women the prevalence was 20.4%. CONCLUSIONS: Anemia in women of childbearing age is a growing public health problem that justifies the implementation of interventions for its prevention and control. OBJETIVO: Cuantificar la prevalencia y distribución de anemia de las mujeres en edad fértil (12 a 49 años de edad) captadas en la Encuesta Nacional de Nutrición 1999 (ENN-99). La Encuesta tuvo un diseño probabilístico y es representativa del ámbito nacional mexicano, de zonas urbanas y rurales y de cuatro regiones: norte, centro, Ciudad de México y sur. MATERIAL Y MÉTODOS: La concentración de hemoglobina se determinó en sangre capilar mediante un fotómetro portátil (HemoCue) en 17 194 mujeres, de las cuales 697 estaban embarazadas. RESULTADOS: La prevalencia de anemia en el ámbito nacional fue de 27.8% para mujeres embarazadas y 20.8% para no embarazadas. Se encontró una mayor prevalencia en zonas rurales que en urbanas, tanto en mujeres embarazadas (28.0% vs 27.7%) como en no embarazadas (22.6% vs 20.0%) pero las diferencias no fueron estadísticamente significativas (p>0.05). La región sur presentó la mayor prevalencia de anemia ( 23.2%), seguida de la región norte (20.9%), la centro (20.6%) y la Ciudad de México (16.4%). Las mujeres no embarazadas indígenas presentaron una prevalencia de anemia de 24.8%, mientras que en las no indígenas fue de 20.4%, no siendo esta diferencia estadísticamente significativa. CONCLUSIONES: La anemia en mujeres en edad fértil es un problema de salud pública que justifica la implantación de programas de prevención y control.